ASAS-ASAS UMUM KEBIJAKSANAAN LINGKUNGAN DALAM UNDANG-UNDANG NO. 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP (UUPPLH) - A'an Efendi (Fakultas Hukum Universitas Surabaya, 2018)
The function of environmental law in action to protect the environment is to place environmental policy in environmental legislation. In order to make environmental legislation effective ini action based on general principles of environmental policy, they are abatement at the source, best practicable means/best technical means, polluter pays principle, stand still principle, Principle oj regional differentiation and shifting of burden of proojlhet beginsel van de omkering van de bewijslast.